Design and validation of an adaptive Cubesat transmitter system using a Thermal Vacuum Chamber (TVAC) - Jaswar, Fitri Dewi; Abd. Rahman, Tharek; Ahmad, Yasser Asrul (2019)
CubeSat in a low earth orbit primarily uses a UHF transmitter with a fixed RF output power. In this paper, the design of the CubeSat transmitter with adaptive power controlability is presented. The design drive is to optimise the SNR and overcome the variability of the propagation path length due to different ground station elevation angles by adjusting its transmitting power. The TVAC test is conducted to validate the performance of the adaptive function in the transmitter. The TVAC is used to emulate the satellite condition in an outer space environment. Four thermal cycles starting from +60°C to -20°C with less than 10-5Pa pressure condition are employed, which was conducted at the KIT CeNT, Japan. The transmitter was integrated inside the satellite structure as a complete CubeSat system. The output power of the transmitter is tested from 0.5W to 2W based on the proposed satellite adaptive mode. The frequency stability of the transmitter is monitored and complies with an average of 70% below requirement, which is less than 2ppm. The results indicate that the RF output power is adjustable to operate as the proposed CubeSat adaptive transmitter in a thermal vacuum condition, which was first developed in Malaysia.